Artificial Intelligence for Knowledge Management : 4th IFIP WG 12.6 International Workshop, AI4KM 2016, Held at IJCAI 2016, New York, NY, USA, July 9, 2016, Revised Selected Papers /: 4th IFIP WG 12.6 International Workshop, AI4KM 2016, Held at IJCAI 2016, New York, NY, USA, July 9, 2016, Revised Selected Papers. (2018) - Unknown
No abstract available